Pengaruh Digital Marketing dan Customer Relationship Marketing Terhadap Customer Loyalty Pada Laughing Buddha Bar Ubud - Tjokorda Gde Agung Wijaya Kesuma Suryawan; Ni Kadek Enny Purwati; Made Mulia Handayani; I Wayan Meryawan (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
Customer Loyalty is an effort to create and maintain customers. Companies need to know to what extent they have Customer Loyalty and to make efforts to increase it. One factor in optimizing Customer Loyalty at Laughing Buddha Bar is through Digital Marketing and implementing Customer Relationship Marketing. The purpose of this study is to determine the partial and simultaneous effect of Digital Marketing and Customer Relationship Marketing on Customer Loyalty at Laughing Buddha Bar in Ubud. This study uses accidental sampling method with a sample of 96 respondents. This method is done by selecting respondents who are met at the time of the research, and using quantitative methods with survey research. Data collection techniques used include observation, interviews, questionnaires and documentation studies. All data are considered valid and reliable with research instrument tests (validity test and reliability test) and can then be analyzed using multiple linear regression analysis, coefficient of determination analysis, and hypothesis testing (t-test and F-test). The results of the study showed that there was a positive and significant influence both partially and simultaneously between Digital Marketing and Customer Relationship Marketing on Customer Loyalty at Laughing Buddha Bar in Ubud.